THE INFLUENCE OF ENTREPRENEUR KNOWLEDGE, FAMILY EXPERIENCE WITH BUSINESS, ENTREPRENEURIAL EDUCATION ON THE INTEREST OF STUDENT ENTREPRENEURSHIP IN UKM UNIVERSITAS SAM RATULANGI - Mambu, Christie Natalia; Pangemanan, Sifrid S.; Pandowo, Merinda . (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: The indicators for measuring entrepreneurial knowledge in this study were obtained through the documentation of entrepreneurship subject grade in Faculty of Economics and Business students. This study takes an object of research at UKM Unsrat. Entrepreneurial knowledge can shape the mindset, attitudes and behaviors of being a true entrepreneur. Establishing them to choose entrepreneurship as a career choice as well as family experience with a business that is significant to the interests of entrepreneurship, educational entrepreneurship at the same time. This research was processed by multiple linear regression methods with the number of respondents 142 students, from a total of 220 students as the population found from the results of regression equation that Entrepreneurial independent variable (X1), Family and Business Experience (X2) and Entrepreneurship Education (X3) have a positive and significant influence and can be concluded, namely Entrepreneurship Knowledge, Family Experience and Business, Positive Entrepreneurship Education, significant with student entrepreneurship. Suggestion: given the Entrepreneur Knowledge and Family Experience With Business and make a significant contribution to Student Entrepreneurial Interest at UKM Unsrat, then UKM Unsrat must pay attention to these factors.Â Keywords: entrepreneur knowledge, family experience with business, entrepreneurial education, interest in student entrepreneurship.